Baseline monitoring of organic sunscreen compounds along South Carolina's coastal marine environment. Issue 1 (15th December 2015) - Bratkovics, Stephanie; Wirth, Edward; Sapozhnikova, Yelena; Pennington, Paul; Sanger, Denise
Abstract: Organic ultraviolet filters (UV-F) are increasingly being used in personal care products to protect skin and other products from the damaging effects of UV radiation. In this study, marine water was collected monthly for approximately one year from six coastal South Carolina, USA sites and analyzed for the occurrence of seven organic chemicals used as UV filters (avobenzone, dioxybenzone, octocrylene, octinoxate, oxybenzone, padimate-o and sulisobenzone). The results were used to examine the relationship between beach use and the distribution of UV-F compounds along coastal South Carolina, USA. Five of the seven target analytes were detected in seawater along coastal South Carolina during this study. Dioxybenzone and sulisobenzone were not detected. The highest concentrations measured were > 3700 ng octocrylene/L and ~ 2200 ng oxybenzone/L and beach use was greatest at this site; a local beach front park. Patterns in concentrations were assessed based on season and a measure of beach use. Highlights: Organic UV filtering (UV-F) chemicals were detected along the SC, USA coast during a 12 month study. Octocrylene and oxybenzone were detected at > 3700 ng/L and ~ 2200 ng/L respectively. As beach use increased, concentrations of UV-F chemicals increased. There were marked seasonal levels and patterns of UV-F reported.